Association of Conventional Cardiovascular Risk Factors With Cardiovascular Disease After Hypertensive Disorders of Pregnancy: Analysis of the Nord-Trøndelag Health Study - Haug, Eirin B. (JAMA Cardiol, 2019)
IMPORTANCE: Women with a history of hypertensive disorders of pregnancy (HDP) have higher risk of cardiovascular disease (CVD). It is not known how much of the excess CVD risk in women with a history of HDP is associated with conventional cardiovascular risk factors. OBJECTIVE: To quantify the excess risk of CVD in women with a history of HDP and estimate the proportion associated with conventional cardiovascular risk factors. DESIGN, SETTING, AND PARTICIPANTS: Prospective cohort study with a median follow-up of 18 years. Population-based cohort of women participating in the Nord-Trøndelag Health Study in Norway. We linked data for 31 364 women from the Nord-Trøndelag Health Study (1984-2008) to validated hospital records (1987-2015), the Cause of Death Registry (1984-2015), and the Medical Birth Registry of Norway (1967-2012). A total of 7399 women were excluded based on selected pregnancy characteristics, incomplete data, or because of emigrating or experiencing the end point before start of follow-up, leaving 23 885 women for study. Data were analyzed between January 1, 2018, and June 6, 2018. EXPOSURES: Experiencing 1 or more pregnancies complicated by HDP before age 40 years vs only experiencing normotensive pregnancies. MAIN OUTCOMES AND MEASURES: We used Cox proportional hazards models to estimate the hazard ratios (HRs) for the association between HDP and CVD. The proportion of excess risk associated with conventional cardiovascular risk factors was estimated using an inverse odds ratio weighting approach. RESULTS: Our study population consisted of 23 885 parous women from Nord-Trøndelag County, Norway. A total of 21 766 women had only normotensive pregnancies, while 2199 women experienced ever having an HDP. From age 40 to 70 years, women with history of HDP had an increased risk of CVD compared with women with only normotensive pregnancies (HR, 1.57; 95% CI, 1.32-1.87) but not at older age (β = 0.98; 95% CI, 0.96-1.00; P for interaction by age = .01). Blood pressure and body mass index were associated with up to 77% of the excess risk of CVD in women with history of HDP, while glucose and lipid levels were associated with smaller proportions. CONCLUSION AND RELEVANCE: In this study, the risk of excess CVD in women with history of HDP was associated with conventional cardiovascular risk factors, indicating that these risk factors are important targets for cardiovascular prevention in these women.